Metabolic bone disease. Issue 5 (October 2017) - Peters, Jonathan; Robertson, Alastair; Godavitarne, Charles; Rogers, Benedict
Abstract: Metabolic bone disease encompasses a diverse group of disorders associated with altered calcium and phosphorous homoeostasis. Although many of these disorders are quite common, they may be difficult to distinguish on the basis of history, physical examination and imaging studies. In clinical practice, metabolic bone disease is often silent until the patient presents with a fracture which is the ultimate complication of many metabolic bone disorders. However, other patients present with a clinical history of back pain and non-specific radiological findings of osteopenia. It is at this stage, that thorough understanding of these diverse manifestations and an accurate diagnosis is crucial to provide the best outcomes for patients with these potentially debilitating disorders. This article aims to give a thorough and succinct review of more relatively common of these diseases.